Human resource management - DeCenzo, David A. (Wiley, 2002)
This text features a real-world perspective that gives readers a clear picture of what today's human resources management is really like. Emphasizing the application of theory, this edition integrates real-world examples from newsworthy corporations to bring concepts to life.